Medio Oriente en la política soviética durante la guerra fría - Ulianova, Olga (Revista de Estudios Árabes, 2014)
The article highlights the USSR role during the Cold War in the Middle East, a region that was the main competing ground for petrol and a strategic location for the only two super-powers.Trying to have a political base in that area, Stalin supported the creation of Israel, but as this country stood firmly on the American side, the USSR shifted its interests to the emerging nationalist Arab countries, helping them financially and providing weapons and man power to the communist parties in the Middle East. Multi-billion military contracts were signed with governments of the region and with it the USSR gained political leverage vis a vis the U.S.A. in the Middle East. Positive results were the independence that some of these countries obtained from colonial rule and a better standing of Arab countries in the world community.